Sex-Based Differences in Factors Associated With Sugar-Sweetened Beverage Consumption Among Korean High School Students - Ra, Jin Suk; Park, Moonkyoung (Frontiers in Nutrition, 2022)
This study aimed to identify sex-based differences in the individual and environmental factors associated with sugar-sweetened beverage (SSB) consumption among Korean high school students. Secondary data were obtained from the 15th (2019) Korea Youth Risk Behavior Web-based Survey. In this study, we analyzed data from 13,066 high school students (5,874 boys and 7,192 girls) who answered questions regarding SSB consumption and individual and environmental factors. Complex sampling analysis (descriptive statistics and logistic regression analysis) was conducted using the SPSS Statistics 26.0 software. Most adolescents (97% boys and 95.2% girls) reported having consumed SSBs in the last seven days. Individual factors, such as increased stress, sleep dissatisfaction, and fast-food intake (more than thrice a week) were positively associated with SSB consumption among adolescent boys and girls. Environmental factors like high education levels (above college) of mothers were negatively associated with SSB consumption among both boys and girls. Furthermore, current alcohol consumption, smoking, low vegetable intake (less than thrice a week) in boys, and more than two hours a day of screen-based sedentary behavior in girls were positively associated with SSB consumption. According to the results, individual factors associated with SSB consumption varied according to the sex of adolescents. Thus, sex differences in factors associated with SSB consumption in adolescents should be considered as basic knowledge for developing strategies for reducing SSB consumption.